2017
DOI: 10.1186/s12888-017-1474-0
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators in accessing dementia care by ethnic minority groups: a meta-synthesis of qualitative studies

Abstract: BackgroundIt is estimated that there are about 25,000 people from UK ethnic minority groups with dementia. It is clear that there is an increasing need to improve access to dementia services for all ethnic groups to ensure that everyone has access to the same potential health benefits. The aim was to systematically review qualitative studies and to perform a meta-synthesis around barriers and facilitators to accessing care for dementia in ethnic minorities.MethodsDatabases were searched to capture studies on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
142
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(154 citation statements)
references
References 45 publications
12
142
0
Order By: Relevance
“…Another consideration is the significant unmet need of the diaspora population from LMICs. In the UK, for example, according to the 2011 consensus, South Asians comprise about 5% of the total population [20] and yet are significantly under-represented within the National Health Service's memory or dementia services [21,22]. Furthermore, even if older South Asians do present to services, their condition is often significantly advanced, and care burden may already have escalated.…”
Section: Introductionmentioning
confidence: 99%
“…Another consideration is the significant unmet need of the diaspora population from LMICs. In the UK, for example, according to the 2011 consensus, South Asians comprise about 5% of the total population [20] and yet are significantly under-represented within the National Health Service's memory or dementia services [21,22]. Furthermore, even if older South Asians do present to services, their condition is often significantly advanced, and care burden may already have escalated.…”
Section: Introductionmentioning
confidence: 99%
“…1 Services may not, however, reach everyone who needs them due to barriers associated with availability, accessibility and acceptability. [10][11][12] This body of evidence is predominantly descriptive, with insufficient attention to understanding causes and processes. 2,3 Since disadvantaged groups have a higher risk of developing dementia, 4 it is especially important to identify the extent of inequities in service access and to understand how best to address these (we use the term inequity to refer to an inequality that is likely to be seen as unfair).…”
Section: Introductionmentioning
confidence: 99%
“…2,5 A small number of qualitative studies identify barriers to accessing dementia care, including poor knowledge, poor/inappropriate service provision and impact of cultural beliefs and previous experiences. [10][11][12] This body of evidence is predominantly descriptive, with insufficient attention to understanding causes and processes. 13 Public Health England, for example, recently recommended that "qualitative research into the differential access of health services by different ethnic groups mediated by different cultural beliefs is needed" and that "these studies should include the identification of barriers and enablers for those communities".…”
Section: Introductionmentioning
confidence: 99%
“…The North West Coast region contains some of the most disadvantaged neighbourhoods in England . It has been found that being from a low socio‐economic background, which can include unemployment, low income, low levels of education and belonging to a minority ethnic group, is associated with receiving different levels of access to and utilization of health‐care services . This can be due to distances to services, but also due to reduced levels of health literacy, and thus knowing when and where to access the right services and which types of services are available …”
Section: Introductionmentioning
confidence: 99%
“…8 It has been found that being from a low socio-economic background, which can include unemployment, low income, low levels of education and belonging to a minority ethnic group, is associated with receiving different levels of access to and utilization of health-care services. 9,10 This can be due to distances to services, but also due to reduced levels of health literacy, and thus knowing when and where to access the right services and which types of services are available. 11,12 The North West Coast Household Health Survey (HHS) is imple- should feedback on the involvement to those who have contributed their time as public advisers to the research.…”
Section: Introductionmentioning
confidence: 99%